Characterization of the Heat Affected Zone in Gas Tungsten Arc Welds of Unalloyed Austempered Ductile Iron - Karaaslan, Ahmet; Akca, Cem (CARL HANSER VERLAG, 2008)
Austempered ductile iron (ADI) exhibits a wide range of mechanical properties depending on the austempering conditions. It is thus extremely important to evaluate the different characteristics of ADI welds where joining is inevitable. In this study, unalloyed ferritic-pearlitic ductile iron specimens which contain 3.69% C, 2.47% Si and 0.2% Mn were austempered in different temperatures to obtain an upper and lower bainitic microstructure and then welded using Gas Tungsten Arc Welding (GTAW) without filler. The results showed that the lower and upper bainitic ADIs can be welded successfully without any crack formation in the heat affected zone (HAZ). It was also observed that the HAZ of the specimen which have been austempered at 275 degrees C for 60 min exhibit a higher hardness than that austempered at 375 degrees C. As the critical austempering time for a homogeneous HAZ characteristic 100 min has been identified.
Keywords: Materials Science